-43+x=23-2x

Simple and best practice solution for -43+x=23-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -43+x=23-2x equation:


Simplifying
-43 + x = 23 + -2x

Solving
-43 + x = 23 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-43 + x + 2x = 23 + -2x + 2x

Combine like terms: x + 2x = 3x
-43 + 3x = 23 + -2x + 2x

Combine like terms: -2x + 2x = 0
-43 + 3x = 23 + 0
-43 + 3x = 23

Add '43' to each side of the equation.
-43 + 43 + 3x = 23 + 43

Combine like terms: -43 + 43 = 0
0 + 3x = 23 + 43
3x = 23 + 43

Combine like terms: 23 + 43 = 66
3x = 66

Divide each side by '3'.
x = 22

Simplifying
x = 22

See similar equations:

| 33.6=H^(3/2) | | 2w+10=48 | | 6x+2(5x-5)=8-3(2x+1) | | 60=256-x | | 5.9h+2.15=20 | | 3x+23+7x-37=180 | | 1-4cosx=-3 | | 73=-6g+97 | | 33.6=H^3/2 | | 8p=97 | | j+23=3 | | 12=6a+2 | | 3x+7y+23=30 | | m=(h-w)/8 | | 7=6c+1 | | 3+4(t+2)=2t-2 | | -y+244=179 | | j+23=-s | | 11+4x+2+3x=90 | | P-3+8=8 | | 0.5(3z+7)+17.7=0.7(3z-4) | | -0.72m=-2 | | 73=9h+1 | | A+B=4X-2 | | 14-3p+1=4+p | | 3.33=-.5 | | 185=35-x | | 750+0.2=1050 | | A+B=4X-8 | | (5.3x+8.2y)+(13.3y-4.1x)= | | 0=8n+7n | | 5x-7.1111=64 |

Equations solver categories